Successful defibrillation verification in subcutaneous implantable cardioverter‐defibrillator recipients by low‐energy shocks. Issue 6 (25th April 2019) - Biffi, Mauro; Ziacchi, Matteo; Angeletti, Andrea; Castelli, Andrea; Massaro, Giulia; Martignani, Cristian; Lovecchio, Mariolina; Valsecchi, Sergio; Diemberger, Igor
Abstract: Background: The subcutaneous implantable cardioverter‐defibrillator (S‐ICD) is an effective alternative to the transvenous one. Defibrillation efficacy depends on maximum device output and on the optimal device location at device implantation. Hypothesis: We sought to investigate the defibrillation safety margin in real life clinical practice. Methods: We sought to understand what is the efficacy of induced ventricular fibrillation (VF) termination at S‐ICD implantation using lower energies than the recommended 65 J. Results: Sixty‐four consecutive S‐ICD recipients underwent VF termination attempts at implantation with energies ranging from 20 to 50 J. Overall, VF termination occurred in 84% of patients with ≤40 J, in 88% with 45 J, and in 100% with 60 J. Intermuscular S‐ICD placement was associated with 94% VF termination at ≤40 J. An ejection fraction <35% was associated to higher energy requirement for defibrillation; however, an intermuscular S‐ICD placement conferred 90% defibrillation efficacy at 31 ± 5 J in this patients subset. Conclusions: This is a hypothesis‐generating observation that prompts a methodologically correct investigation to prove that a 60 J output S‐ICD can provide an adequate safety margin to terminate VF in clinical practice. This would enable superior device longevity and/or device downsizing for pediatric/small size patients.